2019
DOI: 10.1002/jso.25510
|View full text |Cite
|
Sign up to set email alerts
|

Physical function and pain intensity in patients with metastatic bone disease

Abstract: Background Patient reported outcome data in bone metastatic disease are scarce and it would be useful to have normative data and understand what patients are at risk for poor function and more pain. Objectives We aimed to assess what factors are independently associated with physical function and pain intensity in patients with bone metastasis. Methods We included data from 211 patients with bone metastasis who completed a survey (2014‐2016) including the PROMIS Physical Function Cancer and PROMIS Pain Intensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…B one is a common site of metastasis in many types of cancer and can lead to devastating skeletal-related events such as hypercalcemia, pathologic bone fractures, metastatic epidural spinal cord compression, and bone pain (1,2). These events are associated with decreased physical function and quality of life (3)(4)(5). Objectives in treating patients with bone metastases include prevention of skeletal complications, palliation of pain, and maintaining quality of life.…”
mentioning
confidence: 99%
“…B one is a common site of metastasis in many types of cancer and can lead to devastating skeletal-related events such as hypercalcemia, pathologic bone fractures, metastatic epidural spinal cord compression, and bone pain (1,2). These events are associated with decreased physical function and quality of life (3)(4)(5). Objectives in treating patients with bone metastases include prevention of skeletal complications, palliation of pain, and maintaining quality of life.…”
mentioning
confidence: 99%
“…Cross-sectional studies of bone metastases arising from any primary cancer found that pain from bone metastases is associated with poorer HRQOL and worse physical function. 24 , 25 Among the 174 patients with bone metastases in Japan surveyed by Shinoda, et al, 24 the mean EQ-5D quality of life (QOL) score was found to be 0.58, lower than the population average of 0.85. Additionally, although physical function tends to worsen as patients’ pain intensity increases, the correlation between these two outcomes was reported as moderate in a study of 211 patients with cancer pain due to bone metastases.…”
Section: Impact Of Cancer Pain Due To Bone Metastases On Hrqolmentioning
confidence: 99%
“…Additionally, although physical function tends to worsen as patients’ pain intensity increases, the correlation between these two outcomes was reported as moderate in a study of 211 patients with cancer pain due to bone metastases. 25 The authors could not definitively state that there was a causative relationship between pain intensity and physical function because of the presence of confounding variables (eg, tumor histology, disabling conditions). Higher bone pain severity was associated with significantly lower scores on the European Organisation for Research and Treatment of Cancer Quality of Life Questionnaire–Core (EORTC QLQ-C30) generic cancer ( Table 2 ).…”
Section: Impact Of Cancer Pain Due To Bone Metastases On Hrqolmentioning
confidence: 99%
“…Although the MSTS is one of the most commonly used scoring systems in orthopedic oncology practices and has been translated into a few languages, 12–15 it does not properly assess the quality of life in these patients 16 (Table 1). Furthermore, previous studies have demonstrated that clinicians may overestimate a patient's functional results and mental health while underestimating the patient's pain, highlighting the significant shortcomings of reporting patient outcomes without the patient's perspective 17–19 …”
Section: Orthopedic Oncology‐specific Measuresmentioning
confidence: 99%
“…Furthermore, previous studies have demonstrated that clinicians may overestimate a patient's functional results and mental health while underestimating the patient's pain, highlighting the significant shortcomings of reporting patient outcomes without the patient's perspective. [17][18][19] To address the need for an instrument to measure functional status in orthopedic oncology patients from the patient perspective, the Toronto Extremity Salvage Score (TESS) was developed. The TESS evaluates physical disability as reported by the patient following limb preservation surgery for extremity tumors.…”
Section: Orthopedic Oncology-specific Measuresmentioning
confidence: 99%